Antagonistic activity of Ocimum sanctum L. essential oil on growth and zearalenone production by Fusarium graminearum in maize grains - Kalagatur, Naveen K.; Mudili, Venkataramana; Siddaiah, Chandranayaka; Gupta, Vijai K.; Natarajan, Gopalan; Sreepathi, Murali H.; Vardhan, Batra H.; Putcha, Venkata L. R. (Frontiers in Microbiology, 2015)
The present study was aimed to establish the antagonistic effects of Ocimum sanctum L. essential oil (OSEO) on growth and zearalenone (ZEA) production of Fusarium graminearum. GC-MS chemical profiling of OSEO revealed the existence of 43 compounds and the major compound was found to be eugenol (34.7%). DPPH free radical scavenging activity (IC50) of OSEO was determined to be 8.5µg/mL. Minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of OSEO on F. graminearum were recorded as 1250 µg/mL and 1800 µg/mL, respectively. Scanning electron microscope observations showed significant micro morphological damage in OSEO exposed mycelia and spores compared to untreated control culture. Quantitative UHPLC studies revealed that OSEO negatively effected the production of ZEA; the concentration of toxin production was observed to be insignificant at 1500 µg/mL concentration of OSEO. On other hand ZEA concentration was quantified as 3.23 µg/mL in OSEO untreated control culture. Reverse transcriptase qPCR analysis of ZEA metabolic pathway genes (PKS4 and PKS13) revealed that increase in OSEO concentration (250 µg/mL to 1500 µg/mL) significantly downregulated the expression of PKS4 and PKS13. These results were in agreement with the artificially contaminated maize grains as well. In conlusion, the antifungal and antimycotoxic effects of OSEO on F. graminearum in the present study reiterated that, the essential oil of O. sanctum could be a promising herbal fungicide in food processing industries as well as grain storage centers.